2000
DOI: 10.1054/bjoc.1999.0970
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and telomerase activity in malignant lymphomas at diagnosis and relapse

Abstract: Telomere length maintenance, in the vast majority of cases executed by telomerase, is a prerequisite for long-term proliferation. Most malignant tumours, including lymphomas, are telomerase-positive and this activity is a potential target for future therapeutic interventions since inhibition of telomerase has been shown to result in telomere shortening and cell death in vitro. One prerequisite for the suitability of anti-telomerase drugs in treating cancer is that tumours exhibit shortened telomeres compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
(32 reference statements)
4
27
2
Order By: Relevance
“…In these studies, increased telomerase activity was found in B-NHL compared to reactive lymph nodes. Furthermore, a positive correlation of telomerase activity with the rate of proliferation in the B-NHL was found (Norrback et al, 1996;Brousset et al, 1997;Ely et al, 2000;Remes et al, 2000;Lin et al, 2001). In contrast to these studies, we did not find an upregulation of telomerase activity in most of the NHL compared to reactive lymph node tissue (Norrback et al, 1996).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In these studies, increased telomerase activity was found in B-NHL compared to reactive lymph nodes. Furthermore, a positive correlation of telomerase activity with the rate of proliferation in the B-NHL was found (Norrback et al, 1996;Brousset et al, 1997;Ely et al, 2000;Remes et al, 2000;Lin et al, 2001). In contrast to these studies, we did not find an upregulation of telomerase activity in most of the NHL compared to reactive lymph node tissue (Norrback et al, 1996).…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, tumours with low telomerase activity also can be sensitive to telomerase inhibition if (ii) telomeres of the tumour are significantly shorter than telomeres of normal tissue, especially of stem cells. In this case, inhibition of telomerase activity would shorten tumour telomeres faster to a critical length than in normal tissue and would therefore induce cell death selectively in tumour cells (Remes et al, 2000). Adding a new layer of complexity, we demonstrate, that telomere-binding protein expression varies in NHLs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…40 In our study, 8 tumors were treated before sampling. Remes et al 41 showed that telomere length and TA in relapsing malignant lymphomas may vary significantly after the administration of radiotherapy or chemotherapy as compare to nontreated tumors. In another study, 42 TA (but not hTERT) has been shown to be downregulated after chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%